Methods and possibilities of using modern information technology in the field of psychodiagnostics (MMIT Proceedings, 2024)
The article reflects on the advantages and methods of implementation of the use of modern Information Technology in the sphere of psychodiagnostics, as well as on the optimization of its process in measuring the criteria of psychometrics. Known to all of us, today the use of modern information technologies, computer programs in every aspect of our life is becoming a necessity. It is from these requirements that the psychodiagnostics shows the characteristics of a computer program, indicators of efficiency, designed to give a clear, quick and optimal result when measuring psychometric criteria for modified methodologies.